COMPARISON OF SELECTED MOTOR SKILLS AND BODY COMPOSITION CHARACTERISTICS OF PROFESSIONAL AND AMATEUR FOOTBALL PLAYERS - Cem Sinan Aslan; Ender Eyuboğlu; İzzet Karakulak (ümit doğan üstün, 2018)
The study was aimed to compare the footballers from Turkish Super League and Super Amateur League in terms of body compositions and motor skills. 30 professional footballers from super league level and 30 amateur footballers who have played for champion amateur teams participated in the study voluntarily. Body compositions of the participants were measured by Tanita TBF300 (Japan), leg strength by Takei dynamometer (Japan), vertical jump by Takei jump meter (Japan) and range of motion by sit-reach test. Anaerobic power was calculated with Lewis Formula. Motor skills measurements were repeated twice with five minutes' intervals and the highest values were recorded. The data were analyzed by t-test of SPSS at 95% confidence level. As a result, it was found that professional footballers have higher results in age, body weight, height, fat-free mass, leg strength, range of motion and anaerobic power however, no differences were found between the groups on the variables body mass index, body fat mass and percentage, vertical jump and relative strength characteristics.